Cognitive Phenotype and Differential Gene Expression in a Hippocampal Homologue in Two Species of Frog. (15th May 2020) - Liu, Yuxiang; Jones, Corbin D; Day, Lainy B; Summers, Kyle; Burmeister, Sabrina S
Synopsis: The complexity of an animal's interaction with its physical and/or social environment is thought to be associated with behavioral flexibility and cognitive phenotype, though we know little about this relationship in amphibians. We examined differences in cognitive phenotype in two species of frog with divergent natural histories. The green-and-black poison frog ( Dendrobates auratus ) is diurnal, displays enduring social interactions, and uses spatially distributed resources during parental care. Túngara frogs ( Physalaemus=Engystomops pustulosus ) are nocturnal, express only fleeting social interactions, and use ephemeral puddles to breed in a lek-type mating system. Comparing performance in identical discrimination tasks, we find that D. auratus made fewer errors when learning and displayed greater behavioral flexibility in reversal learning tasks than túngara frogs. Further, túngara frogs preferred to learn beacons that can be used in direct guidance whereas D. auratus preferred position cues that could be used to spatially orient relative to the goal. Behavioral flexibility and spatial cognition are associated with hippocampal function in mammals. Accordingly, we examined differential gene expression in the medial pallium, the amphibian homolog of the hippocampus. Our preliminary data indicate that genes related to learning and memory, synaptic plasticity, and neurogenesis were upregulated in D. auratus, while genes related to apoptosis were upregulated in túngara frogs, suggesting that these cellular processes could contribute to the differences in behavioral flexibility and spatial learning we observed between poison frogs and túngara frogs.